Fabrication of Green Diatomite/Chitosan-Based Hybrid Foams with Dye Sorption Capacity - Galzerano, Barbara (2020)
The latest tendency of the scientific community regards the development of different classes of green materials able to solve pollution problems caused by industrial and human activity. In this paper, chitosan and diatomite were used to produce a broad-spectrum hybrid adsorbent, either in powder or in monolithic form for environmental pollutant removal. Diatomite-chitosan-based powders and porous diatomite-chitosan hybrids were prepared and characterized by chemical-physical, thermal and morphological analysis. Moreover, their adsorbent capacity towards anionic dye (Indigo Carmine) was also evaluated. Obtained data showed that chitosan improves the adsorption capacity of both systems, increasing the uptake of dye in both diatomite-chitosan systems.